Piano Sonatas. Dublin: C. E. Music. Ed. Esposito (BGPS 142) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::; Esposito, M. (Michele), 1855-1930:::Contributor::: (Dublin; Ireland; C. E. Music, 2024)
First volume of a collection of the piano sonatas edited by Michele Esposito, containing opp. 2 through 7.